IDDF2022-ABS-0015 Effect of comprehensive nursing intervention on stress and psychological status of children and their families during ercp perioperative period. (2nd September 2022) - He, Donghong; Tan, Wenhui
Abstract : Background: To explore the effect of comprehensive nursing intervention on the stress and psychological status of children and their families during ERCP perioperative period. Methods: A total of 100 children undergoing ERCP from January 10, 2018 to October 10, 2019 were selected and divided into the observation group and the control group by lottery, with 50 cases in each group. The two groups were respectively given comprehensive and routine nursing interventions. The stress and complication rate of children during the perioperative period of ERCP were observed, and the anxiety and depression of children's families were scored. Results: In the observation group, 30 cases were mildly stressed (60.00%), and 20 cases were moderately stressed (40.00%). The degree of stress was lower than that of the control group (P<0.05); the complication rate in the observation group was 4.00%, which was lower than that of the control group (P<0.05); the anxiety score (14.01±0.11) and depression score (15.23±1.48) of family members of the observation group were lower than those of the control group (P< 0.05). Conclusions: Comprehensive nursing intervention can effectively reduce the stress of children during the perioperative period of ERCP, reduce the incidence of complications, and improve the negative emotions of the children's family members, thereby promoting early recovery of the children.